Complement Inhibitor Therapy for Myasthenia Gravis - Albazli, Khaled; Kaminski, Henry J.; Howard, James F. (Frontiers in Immunology, 2020)
Complement activation as a driver of pathology in myasthenia gravis (MG) has been appreciated for decades. The terminal complement component [membrane attack complex (MAC)] is found at the neuromuscular junctions of patients with MG. Animals with experimental autoimmune MG are dependent predominantly on an active complement system to develop weakness. Mice deficient in intrinsic complement regulatory proteins demonstrate a significant increase in the destruction of the neuromuscular junction. As subtypes of MG have been better defined, it has been appreciated that acetylcholine receptor antibody-positive disease is driven by complement activation. Preclinical assessments have confirmed that complement inhibition would be a viable therapeutic approach. Eculizumab, an antibody directed toward the C5 component of complement, was demonstrated to be effective in a Phase 3 trial with subsequent approval by the Federal Drug Administration of the United States and other worldwide regulatory agencies for its use in acetylcholine receptor antibody-positive MG. Second- and third-generation complement inhibitors are in development and approaching pivotal efficacy evaluations. This review will summarize the history and present the state of knowledge of this new therapeutic modality.